A high efficiency BPSK receiver for short range wireless network - Mousa Yousefi; Khalil Monfaredi (Universitas Ahmad Dahlan, 2019)
In this paper, a 910MHz high efficiency BPSK receiver is presented with Colpitts oscillator for short range wireless network. In this research, with injection-lock technique and using Colpitts oscillator, the efficiency of receiver has been improved. And also, behavior of an oscillator under injection of another signal has been investigated. Also, variation of output signal amplitude versus injected signal phase variation, the effect of varying the amplitude of injected signal and quality factor of the oscillator has been investigated. The designed receiver has 0.474 mW dc power and -60 dBm sensitivity. Data rate of receiver is 5 Mbps. The FOM of receiver is 94 pJ/bit. This receiver was designed and simulated in 0.18 μm RFCMOS technology. This proposed receiver can be used in short range wireless network for example, Wireless Body array network and wireless sensor network.